THE EFFECTIVENESS OF MIND MAPPING FOR TEACHING VOCABULARY TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 3 SUNGAI KAKAP IN ACADEMIC YEAR 2012/2013 - Sahrawi, Sahrawi (Jurnal Pendidikan Bahasa, 2013)
This study was a pre-experimental research. The purposes of this study were to find out the effectiveness and the significance of mind mapping for teaching English vocabulary. This study was conducted in SMP Negeri 3 Sungai Kakap in academic year 2012/2013 where the population was eighth grade students with a total number of 112 students.The data showed the difference result between pre-test and post-test. The average achievement of the studentsâ pre-test was 46.28 and 86.14 in the post-test. Furthermore, the data showed there was significant difference of the score where the t-test result 31.88. It showed that the result of t-test was higher than t-table (2.052) at 5% with degree of freedom N-1 (28-1). Therefore, it can be suggested that mind mapping can be an effective technique to teach english vocabulary. This result hopefully would motivate english language teachers to use a mind mapping in teaching English in the classroom.Keywords: The Effectiveness, Mind Mapping, Vocabulary